Investigation Of Variation Of Fin Length Dimensions On Piezoelectric Voltage Generating - Riyan Ariyansah; Sunaryo Sunaryo; Sutoyo Sutoyo (Clean Energy and Smart Technology, 2022)
Piezoelectric is one of the generators of electrical energy when the material is deflected due to pressure. Research has been done on the potential of the fins on the electric voltage produced by piezoelectric. The research method used is to observe the piezoelectric vibrating due to the flow of air passing through the bluff body resulting in a deflection of the fins to strike the piezoelectric and measuring the electric voltage. Changes in the speed of fins installed with piezoelectric dimensions, namely fin one length 12 cm and width 10 cm, fin two length 12 cm width 10 cm and tip width 12 cm, fin three length 12 cm, width 10 cm and tip width 14 cm. The research was conducted in a mini wind tunnel with wind speeds of 5 m/s, 7 m/s, and 9 m/s with a piezoelectric distance to the rhombus bluff body is 80 mm. The results obtained are fin 1 with a speed of 9 m/s produces an electric voltage of 5.15 volts, fin 3 with a speed of 9 m/s produces an electric voltage of 5.46 volts, and fin 4 with a wind speed of 9 m/s has the highest voltage value, namely 5.58 volts. The airflow as it passes through the end of the bluff body section causes the fin to move up and down. The greater the turbulence that occurs, the greater the air hitting the piezoelectric surface so that the value of the electric voltage becomes high.